TRANSFORMATION OF SOCIAL ECONOMY LAW: A LITERATURE STUDY ON REGULATORY IMPLEMENTATION AND EFFECTIVENESS - Gunawan Widjaja (CV. Adiba Aisha Amira, 2024)
This research aims to examine the transformation of social economic law, by reviewing various literatures that review the implementation and effectiveness of existing regulations. In the context of this research, legal transformation is considered a dynamic and continuous process that must be able to adjust to the rapidly changing socio-economic environment. The study concludes that an effective regulation in the social economy must be flexible, accessible and responsive to social needs, with an emphasis on community empowerment and broader social interests. In addition, this study highlights the importance of continuous monitoring and evaluation to keep regulations relevant and able to have a positive impact in a sustainable manner.